The effectivity of electrode anesthesia in alleviating pain during a restorative procedure - de Villa, Ma. Glendora H.
A study was conducted to test the effectivity of a modified TENS machine in alleviating pain during a restorative procedure and to determine its acceptability among a group of volunteers. Twenty one patients were randomly selected to undergo Class I or Class III cavity preparations and filling using the modified TENS machine as anesthesia instead of a dental infection. Seven out of twenty one patients were rated successful while fourteen were rated failures. Statistical analysis showed that the proportion of successes is not significantly different from the proportion of failures. Acceptability of the machine acceptable. Similarly, statistical analysis showed that there was no significant difference between the two proportions. The results of the study remain inconclusive. The modified TENS machine has equal chances of success of failure, acceptability or non-acceptability.